Penile Amputation in Genital Self-Mutilation (GSM) due to Dextrometrophan Abuse: Case Report - Yosephine, Fiona; Seno Utomo, Tomy Muhamad; Tampubolon, Kevin Anthony Glorius (Journal of Neonatal Surgery, 2025)
Background: Genital self-mutilation (GSM) is a very rare emergency, usually involving deliberate damage to the genital area. Many factors influence a person to carry out this action, one of which is the use of hallucinogens, such as dextromethorphan. Dextromethorphan is a cough medicine that is easy to find and is often misused. We report a case of a person who mutilated his genitals due to the influence of dextromethorphan. Case Presentation: A 23-year-old man presented to the hospital with an unusual condition: genital mutilation. The patient reported that he mutilated his genitals using scissors after taking 10 cough tablets containing dextromethorphan. He was diagnosed with penile amputation due to GSM. The patient underwent procedures to close the wound on the amputated part of the penis and penile reconstruction surgery. Conclusion: GSM is rare and complex, often linked to psychosis, sociocultural factors, or psychological issues. This case involves GSM induced by dextromethorphan abuse, which has hallucinogenic effects. Treatment includes immediate medical care for the injury and long-term psychiatric support. Preservation and replantation of the amputated penis are crucial. A multidisciplinary approach with urologists and psychiatrists is essential for recovery and prevention